The Effect of Dietary Supplementation with Chaste Tree (Vitex agnus-castus L.) Seed Extract on the Haematological Indices of Rainbow Trout (Oncorhynchus mykiss) - Mohamed Omar Abdalla Salem; Abubaker Dow Abubaker Barkah (African Journal of Advanced Pure and Applied Sciences, 2025)
This research evaluated the influence of incorporating a methanol-water extract from Chaste Tree (Vitex agnus-castus L.) seeds into the diet of Rainbow Trout (Oncorhynchus mykiss) on key blood parameters. Juvenile trout, averaging 4.35 ± 0.16 g in weight, were administered diets supplemented with 0% (control), 0.1%, 0.5%, or 1% extract for 45 days. Post-experiment analyses demonstrated marked increases in hemoglobin concentration, red and white blood cell counts, and hematocrit levels across all treatment groups relative to the control (P < 0.05). The findings imply that Chaste Tree extract may bolster immune responses in Rainbow Trout, highlighting its potential as a hematological enhancer in aquaculture practices.